Rhythm and musical instruments of early Yoruba native airs in christian liturgy (2018)
Rhythm is a central element in African music. The concept of rhythm in European music differs from that of African music. To the Africans, rhythm is engaging and interactive. Therefore, rhythm elicits dance. Drums and percussion instruments play a key role in establishing a rhythm in Yoruba musical ensembles. However, Yoruba drums were associated with idol worship and a relationship with paganistic practices by the European missionaries. Hence, the prohibition of drumming and dancing for several decades in the early Yoruba church constituted a musical challenge to the early Yoruba Christian converts. Within the atmosphere of cultural nationalism of the late 19th and early 20th century, certain churchmen decided to seek alternative indigenous musical idiom to replace the unsatisfactory European type of music with which Christianity was introduced to them. They evolved a distinctive brand of music known as Yoruba native airs. This article is anchored on the theory of intercultural music, as propounded by Euba and Kimberlin, which addresses the phenomenon of musical works deriving from more than one culture. Wọ́rọ̀ rhythm is the most common rhythm employed in the early Yoruba native airs. It is based on a 12/8 compound time signature which produces a graceful rhythmic flow usually associated with Yoruba aristocracy and royalty. The musical instruments employed by the three selected composers are intercultural, which cuts across the four classes of musical instruments used in African ensembles, as well as those utilized in European church music.